Discretization of Optimal Control Problems Governed by p-Laplacian Elliptic Equations - Shu Luan (Journal of Applied Mathematics)
In this paper, a state-constrained optimal control problem governed by p-Laplacian elliptic equations is studied. The feasible control set or the cost functional may be nonconvex, and the purpose is to obtain the convergence of a solution of the discretized control problem to an optimal control of the relaxed continuous problem.